Mapping research findings on change implementation in nursing practice: A scoping literature review - Israa Salma; Mathias Waelli (Wiley, 2023)
Abstract Aims The aim of this study was to map the diverse factors impacting change implementation in nursing practices and investigate different implementation strategies. Design Scoping literature review following PRISMA‐ScR extension. Methods Data were collected from PubMed, Ebsco, Scopus and ScienceDirect databases from 1990 onwards. Only English peer‐reviewed studies reporting an implementation of change in nursing practice were included. Of 9,954 studies, 425 abstracts were scanned and 98 full‐text articles were screened. Finally, 28 studies were selected. Results A multifaceted approach, with a tailored intervention, was the most effective implementation strategy. Most identified factors were considered systematic, for example resource availability, leadership and knowledge. However, others related to local social and material context were identified in fewer number of studies. These seem to be operational elements for implementation processes. Both types of factors are essential and must be considered for successful implementation. Conclusion We advocate the development of framework including systematic factors and which capture the local context flexibility.